Synergistic impacts of global warming and thermohaline circulation collapse on amphibians - Julián A. Velasco (Nature Portfolio, 2021)
Julián Velasco et al. use climate model simulations to show how the collapse of the Atlantic meridional overturning circulation and unabated global warming under the RCP 8.5 scenario affect the global distribution of 2509 amphibian species. These results show severe and synergistic impacts of global warming, with particularly strong effects shown in the Neotropical, Nearctic and Palearctic regions.